Molecular Environmental Soil Science at the Interfaces in the Earth$1 (Bs Critical Zones - Xu, Jianming; Huang, Pan Ming.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Molecular Environmental Soil Science at the Interfaces in the Earth's Critical Zone" presents contributions from the 1st International Symposium of Molecular Environmental Soil Science at the Interfaces in the Earth's Critical Zone held in Hangzhou, China. It introduces new ideas, findings, methods, and experience on above new and emerging subject areas. A broad range of topics are covered: the role of mineral colloids in carbon turnover and sequestration and the impact on climate change, biogeochemical interfacial reactions and dynamics of vital and toxic elements, ecotoxicology of anthropogenic organics, environmental nanoparticles and their impacts, and ecosystem health. The book will be a valuable reference for researchers in soil chemistry, environmental chemistry, mineralogy, microbiology, ecology, ecotoxicology, and physics. Jianming Xu is a Professor at the Institute of Soil and Water Resources and Environmental Science, Zhejiang University, China. Pan Ming Huang is a Professor at the Department of Soil Science, University of Saskatchewan, Canada.
Plenary Lectures by IUPAC Scientists -- The Role of Mineral Colloids in Carbon Turnover and Sequestration and the Impact on Climate Change -- Biogeochemical Interfacial Reactions and the Transformation, Transport and Fate of Vital and Toxic Elements -- Anthropogenic Organics, Crop Protection and Ecotoxicology -- Environmental Nanoparticles: Distribution, Formation, Transformation, Structural and Surface Chemistry, and Biogeochemical and Ecological Impacts -- Environmental Processes and Ecosystem Health.
Keywords: Environmental sciences; Mineralogy; Ecology; Microbiology; Environmental chemistry; Environmental toxicology; Environment; Environmental Chemistry; Mineralogy; Microbiology; Ecotoxicology; Ecology